The longest (A+T) and (G+C) blocks in the human and other genomes - Hrabcová, Iva; Kypr, Jaroslav (Journal of biomolecular structure & dynamics, 2008)
We analysed complete or almost complete nucleotide sequences of the human, chimp, mouse, rat, chicken, dog, and other genomes to find that they contain extremely long (A+T) a (G+C) blocks that do not occur at all in the corresponding randomized sequences. The longest is an (A+T) block containing 1040 consecutive AT pairs that occurs in the 16th human chromosome. The longest human (G+C) block has 261 bp in length. About a half of the longest blocks occur in introns. The (A+T) blocks are discrete units whereas the (G+C) blocks are diffuse. They are imbedded in the genome through connectors longer than 1 kilobase where the (G+C) content gradually decreases to the value of 50%. Remarkably, the (A+T) as well as (G+C) blocks are substantially shorter in the chimp genome. Chicken is characteristic by very long (G+C) blocks that are even longer than in the human genome. Though much shorter, long (G+C) and especially (A+T) blocks occur in lower organisms as well, which means that AT and GC pair clustering is an ancient property that has evolved into large scales in higher eukaryote genomes and the human genome in particular. Very long (A+T) and (G+C) blocks confer specific biophysical properties on DNA that are likely to influence genome folding in cell nuclei and its functional properties.
Keywords: GC Rich Sequence; Mice; Chickens; Dogs; financování organizované; kur domácí; Sequence Analysis, DNA; myši; Rats; AT Rich Sequence; lidé; psi; sekvenční analýza DNA; genom lidský; GC bohatá sekvence; Financing, Organized; zvířata; krysa rodu Rattus; Humans; oblasti bohaté na AT; Animals; Pan troglodytes; Genome, Human